Inequality and mobility analysis by the Hungarian Rotation Panel, 1993-98 - Zsuzsa Kapitany; Gyorgy Molnar (Hungarian Academy of Sciences, Institute of Economics, 2002)
We investigate the trends of inequalities and mobility of income, expenditure and stock of durables between 1993 and 1998 in Hungary. In 1996-8 the stagnating level of inequalities is coupled with relatively low and decreasing mobility. The relationship between inequalities and mobility fastens the relative positions of households, increasing the share of households unable to improve their positions on the short term. The impacts of the stabilisation shock in 1995 are shown with the help of the Hungarian Rotation Household Panel, a new dataset based on Household Budget Surveys. We give a detailed description of the Rotation Panel.
Keywords: 330